The impact of knowledge management processes on information systems: A systematic review - Al-Emran, Mostafa; Mezhuyev, Vitaliy; Adzhar, Kamaludin; Shaalan, Khaled (Elsevier Ltd, 2018)
Knowledge Management (KM) processes play a significant role in the implementation of various Information Systems (IS). Several review studies were carried out to afford a better understanding of the current research trend of KM processes. However, this issue still needs to be examined from other perspectives. It is observed that previous research neglects the examination of KM processes studies with regard to ISs. The current study systematically reviews and sheds the light on KM processes studies related to ISs aiming to provide a comprehensive analysis of 41 research articles published in peer-reviewed journals from 2001 to 2018. The main findings of this study indicate that knowledge sharing is the most frequent KM process studied, followed by knowledge acquisition and knowledge application. Besides, questionnaire surveys were found to be the primarily relied research methods for data collection in the context of KM processes. In addition, 78% of the analyzed studies registered positive research outcomes. In terms of IS type, most of the analyzed studies focused on investigating the impact of KM processes on E-business systems, knowledge management systems, and IS outsourcing, respectively. Additionally, in terms of data collection, the majority of the analyzed studies were primarily focused on the participants who are IS executives/managers. Furthermore, most of the analyzed studies that achieved positive outcomes were carried out in China. To that end, this review study attempts to demonstrate and detail the recent increase in the interest and the advancement made in KM processes research considering ISs studies, which form an essential reference for scholars in KM field.